Pengaruh Konflik Kerja dan Stres Kerja Terhadap Turnover Intention Karyawan Pada PT Suriatama Mahkota Kencana (Suzuya) di Pekanbaru - Aritonang, Roi Martin; Joesyiana, Kiki; Mulyana, Sri (Pelantar Press, 2023)
The purpose of this study was to determine the effect of work conflict and work stress on turnover intention at PT Suriatama Mahkota Kencana (Suzuya) in Pekanbaru. The place of this research was carried out at PT Suriatama Mahkota Kencana (Suzuya). The population in this study was 52 respondents, so that the sample was taken using a saturated sampling technique, namely all employees at PT Suriatama Mahkota Kencana. The sample selection used a purposive sampling technique because the population size was relatively small. This research method is quantitative with data collection techniques using a questionnaire and the data is analyzed by multiple linear regression analysis. Based on the results of this study, work conflict affects employee turnover intention at PT Suriatama Mahkota Kencana (Suzuya). Job Stress affects Employee Turnover Intention at PT Suriatama Mahkota Kencana (Suzuya). Work Conflict and Work Stress jointly affect Employee Turnover Intention at PT Suriatama Mahkota Kencana (Suzuya). The variable contribution of Work Conflict and Work Stress to Turnover Intention is 54.3%.